Variations of Elderly Communication: Conversations and Conformity with Children, In-Laws, and Grandchildren - Yulianti; Putri, Dian Widya; Hamdan, Stephani (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2025)
An aging population is a global demographic trend that creates social problems. Whether they live with family members or apart from them, elderly individuals often experience potential conflict in intergenerational communication. This research aims to find out the family communication patterns of the elderly in their communication with children, in-laws, and grandchildren. The Revised Family Communication Pattern Instrument (Parent Version) or RFCP-PV was used to measure family communication patterns that link conversation orientation and conformity orientation. This study used quantitative descriptive methods on 94 elderly people in Bandung City. This elderly group consists of Seroja Cinambo Elderly, Bahagia Antapani Elderly, Sibulan Sukajadi Elderly, and Sicetar Ujung Berung Elderly. The elderly who were used as respondents were elderly people who were under the auspices of Indonesia Friendly Elderly (IRL), West Java. The elderly were asked to complete a questionnaire regarding family communication patterns and provide an overview of variations in their communication with their families. The results indicate diverse patterns in how elderly individuals communicate with their children, in-laws, and grandchildren, particularly regarding their orientation toward conversation and conformity.